Dasatinib targets B-lineage cells but does not provide an effective therapy for myeloproliferative disease in c-Cbl RING finger mutant mice. - Johanna M Duyvestyn; Samuel J Taylor; Samantha A Dagger; Marlene Orandle; Herbert C Morse; Christine B F Thien; Wallace Y Langdon (PLoS ONE, 2014)
This study aimed to determine whether the multi-kinase inhibitor dasatinib would provide an effective therapy for myeloproliferative diseases (MPDs) involving c-Cbl mutations. These mutations, which occur in the RING finger and linker domains, abolish the ability of c-Cbl to function as an E3 ubiquitin ligase and downregulate activated protein tyrosine kinases. Here we analyzed the effects of dasatinib in a c-Cbl RING finger mutant mouse that develops an MPD with a phenotype similar to the human MPDs. The mice are characterized by enhanced tyrosine kinase signaling resulting in an expansion of hematopoietic stem cells, multipotent progenitors and cells within the myeloid lineage. Since c-Cbl is a negative regulator of c-Kit and Src signaling we reasoned that dasatinib, which targets these kinases, would be an effective therapy. Furthermore, two recent studies showed dasatinib to be effective in inhibiting the in vitro growth of cells from leukemia patients with c-Cbl RING finger and linker domain mutations. Surprisingly we found that dasatinib did not provide an effective therapy for c-Cbl RING finger mutant mice since it did not suppress any of the hematopoietic lineages that promote MPD development. Thus we conclude that dasatinib may not be an appropriate therapy for leukemia patients with c-Cbl mutations. We did however find that dasatinib caused a marked reduction of pre-B cells and immature B cells which correlated with a loss of Src activity. This study is therefore the first to provide a detailed characterization of in vivo effects of dasatinib in a hematopoietic disorder that is driven by protein tyrosine kinases other than BCR-ABL.